Combining design of experiments and streamline-based simulation for efficient thermal IOR development study in a waterdrive light oil reservoir - Al-Mudhafer, W.J. (Offshore Technology Conference, 2014)
Steamflooding has been widely applied as an effective way to improve oil recovery not only in heavy oil reservoirs, but also in light oil reservoirs. It has been investigated that Steamflooding is a good way to handle the formation's heterogeneity by decrease the degree of fluid spread and distortion in addition to extract bitumen that might be found in light oil reservoirs as in the reservoir under study. This reservoir is a sandstone formation in South Rumaila oil field located in Iraq. This field, with a 58-year production history, has 40 production wells and is surrounded by an infinite active edge water aquifer from the east and the west flanks. Because of some discontinuous series of bitumen at the east flank, the strength of east flank is much effective less than the west one. In this study, a comparative thermodynamic simulation study has been conducted to investigate the feasibility of Steamflooding to extract the bitumen and improve oil recovery and determine the optimal future development scenario considering design of experiments and streamline-based simulation results. First of all, a thermodynamic reservoir simulator has been used to find out the feasibility of steam flooding in the heteroge-neous reservoir to extract the bitumen and improve oil recovery. Later, full factorial design (FFD) has been conducted to figure out the most factors affecting the response (recovery factor) through Steamflooding with distinct levels. The factors are steam injection rate, quality, temperature, and number of steam injectors. FFD has shown that the recovery factor is sensitive for all the mentioned factors as well as some interactions and it also shown that the optimal scenario has the highest steam quality, injection rate, and temperature with the lowest number of injectors to get the highest recovery factor. Consequently, and in order to determine the optimal number of injectors, a connectivity matrix between the injectors and producers has been constructed to provide a source of potential injection wells to be optimized. This matrix has been set based on the streamline-based simulation results at the first time step of the prediction period and the wells were selected according to the higher connectivity with the producers. This practical optimization approach has led to determine the optimal number of steam injection wells that leads to optimal development scenario. It has shown finally that only one injector, which has higher connections with the main producers in the field, has led to highest oil recovery. Copyright 2014, Offshore Technology Conference.